Rapid Decay of Slowly Moving Typhoon Soulik (2018) due to Interactions With the Strongly Stratified Northern East China Sea. Issue 24 (23rd December 2019) - Park, Jae‐Hyoung; Yeo, Da‐Eun; Lee, KyungJae; Lee, Hojun; Lee, Seung‐Woo; Noh, Suyun; Kim, Seongjung; Shin, JiYun; Choi, Yeon; Nam, SungHyun
Abstract: Typhoon Soulik decayed rapidly via two‐way interaction with the northern East China Sea, the extratropical shelf region, before landing on the Korean Peninsula on 23 August 2018. In the northern East China Sea, where the water column is strongly stratified with warm surface and cold subsurface waters, a large cold wake emerged with intense sea surface cooling, which is primarily caused by vertical mixing in the water column. This abrupt sea surface cooling rapidly increased the downward enthalpy flux, mostly in the form of latent heat flux. The slow translation speed of Typhoon Soulik and strong thermal stratification in the region transferred its energy into the ocean, as the typhoon had a long residence time over the wake, and consequently led to rapid decay with energy loss to typhoon intensity ratio of −4.4 ± 1.0 hPa (kJ cm −2 ) −1 . Plain Language Summary: Understanding and predicting tropical cyclones, including typhoons, are very important for reducing and preventing damages to life and property. In August of 2018, Typhoon Soulik was predicted to make landfall on the Korean Peninsula as a strong cyclone with high winds. However, the typhoon rapidly weakened over the northern East China Sea before making landfall—a failed prediction. This study reveals that the rapid decay was caused by two‐way interactions between the typhoon and the ocean on the continental shelf. Strong mixing with cold subsurface water due to the high winds associated with the slowly moving typhoon significantly lowered the sea surface temperature, leading to energy loss into the ocean for a sufficiently long period of time to cause rapid decay. These results provide quantitative evidence of energy exchange between the typhoon and the ocean, which can help to improve forecasts of tropical cyclone intensity particularly in the stratified shelf region. Key Points: Two‐way interactions between stratified ocean and a slowly translating (~2 m s −1 ) tropical cyclone yields rapid decay Severe (>8 °C) sea surface cooling is primarily caused by vertical mixing with cold subsurface water on the extratropical shelf Rapid decay is driven by downward energy transfer enhanced by Soulik's long (~15‐hr) residence time over a large cold wake